2022
DOI: 10.1103/physrevb.105.245305
|View full text |Cite|
|
Sign up to set email alerts
|

Gate voltage dependent Rashba spin splitting in hole transverse magnetic focusing

Abstract: This is a repository copy of Gate voltage dependent Rashba spin splitting in hole transverse magnetic focusing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…Further, we show that Shubnikov-de Haas oscillations exhibit a weaker band splitting, suggesting that it probes different electron dynamics. Interestingly, a similar behavior was found in studies on 2DEG with SOC 19 , 21 , indicating that this is universal and a new theory is needed to explain the phenomenon. Our study, therefore, places graphene-TMDC heterostructures as an interesting new material platform to explore the effect of SOC on ballistic electron transport in low-dimensional systems.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Further, we show that Shubnikov-de Haas oscillations exhibit a weaker band splitting, suggesting that it probes different electron dynamics. Interestingly, a similar behavior was found in studies on 2DEG with SOC 19 , 21 , indicating that this is universal and a new theory is needed to explain the phenomenon. Our study, therefore, places graphene-TMDC heterostructures as an interesting new material platform to explore the effect of SOC on ballistic electron transport in low-dimensional systems.…”
Section: Introductionsupporting
confidence: 73%
“…3d , e. Therefore, we can estimate that in our system, the Rashba term dominates. Similarly, studies on 2DEG systems with Rashba SOC have indeed shown no splitting in the second focusing peak 19 , 21 , 55 .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In a magnetic focussing measurement, this results in separate cyclotron orbits for each spin and creates a spatial spin separation, splitting the first focussing peak. Previous work has demonstrated the ability to detect a change in peak splitting as the magnitude of the Rashba SOI is changed [19].…”
Section: Magnetic Focussing With a Cubic Rashba Spin-orbit Interactionmentioning
confidence: 99%
“…A recent study investigated magnetic focussing using a device where the Rashba SOI magnitude could be tuned in situ using a top gate voltage (V TG ) [19]. This technique revealed an increase in the spatial separation of the spin-split focussing trajectories as the Rashba SOI was increased.…”
Section: Introductionmentioning
confidence: 99%